ASSA13-14-2 The Influence of Long-Term Regular Vitamin D Intervention to Renin and Renin Receptor in Spontaneously Hypertensive Rats. (29th April 2013) - Xinjuan, Xu; Xiaowei, Qin; Lu, Han; Hong, Lei
Abstract : Objective: To explore the influence of long-term regular vitamin D intervention on rennin and its receptor in spontaneously hypertensive rats. Methods: 20 spontaneously hypertensive rats were randomly divided into two groups. The experimental group received vitamin D3 preparation 3ug/kg dissolved in 0.5ml propylene glycol by intraperitoneal injection (twice a week) for three months; the control group was given the equal volume of propylene glycol alone. Monitor the changes of blood pressure of rats during the experiment every week. Serum was collected after the experiment. Serum 25(OH)D3, calcium, rennin concentration were detected by Enzyme-linked immunosorbent. To explore renin and renin receptor mRNA expression levels in kidney between the two groups by RT-PCR. Renin receptor's expression in kidney and heart was examined by immunohistochemical and computer image analysis. Pathological change was examined by HE staining. Results: The blood pressure of experimental group was lower than that in control group ( P < 0.05). Serum 25 (OH) D3, calcium concentration in experimental group were higher than that in control group ( P < 0.05), while renin level was lower ( P < 0.05). RT-PCR results showed that there was significant difference of renin mRNA expression in kidney in the two groups, which expressed in the experimental group more than that in control group ( P < 0.05). There was no difference of renin receptor mRNA expression between the two groups ( P > 0.05). It found that renin receptor was widely distributed by Immunohistochemical, but there was no difference in the two groups ( P > 0.05). HE staining displayed there was hypertensive pathological changes in control group, but it was not obvious in the experimental group. Conclusions: vitamin D can inhibit renin gene transcription, inhibit hypertensive organ damage, but its effect to renin receptor is not obvious.